Methods for general and molecular microbiology - Reddy, C.A. (ASM Press, 2007)
Provides a comprehensive compendium of methods used in general and molecular microbiology. Contains many new and expanded chapters, including a section on the newly important field of community and genomic analysis. Provides step-by-step coverage of procedures, with an extensive list of references to guide the user to the original literature for more complete descriptions.